Uniting to address paediatric heart disease in Africa: Advocacy from Rwanda - Binagwaho, Agnes; Rusingiza, Emmanuel K.; Mucumbitsi, Joseph; Wagner, Claire M.; Swain, JaBaris D.; Kagame, Abel; Bukhman, Gene; Uwaliraye, Parfait; Nyemazi, Jean Pierre; Nutt, Cameron T.; Bolman, R. Morton; Goldberg, Hal; et al. (SA Heart Journal, 2017)
Paediatric heart disease causes death or disability in 15 million children around the world each year – a fi gure staggeringly disproportionate to available and relevant international funding and support. Although 80% of the burden of cardiovascular disorders fall in low- and middleincome countries, poor countries have a very limited capacity to build a system of care to address heart disease, including prevention, care, control and research. In this article, authors who work in or with Rwanda’s public sector aim to describe the current state of heart disease among children, what is currently being done to manage care and future directions for the national programme. As the world turns its attention to non-communicable diseases and seeks to ensure that they fi nd a prominent place in the post-2015 development agenda, it is essential to ensure that children are not left behind.